Neutrophil-to-albumin ratio as a predictor of mortality in patients with intracerebral hemorrhage: a multicenter retrospective cohort study - Jun Wan; Sen Zhang; Xiang Yuan; Yuyang Liu; Xin Cheng; Hao Liu; Fengrui Yang; Yinquan Ai; Xiaohong Luo; Yuting Zhong; Shiqiao Liu; Yu Zhang (BMC Neurology)
Abstract Background Intracerebral hemorrhage (ICH) is associated with a poor prognosis. The association between the neutrophil-to-albumin ratio (NAR) with mortality in patients with ICH remains underexplored. This study investigated the relationship between the NAR and mortality in patients with ICH. Methods A multicenter retrospective observational cohort study was conducted from January 2010 to June 2019. Participants were divided into four groups according to NAR quartiles at admission. Univariable and multivariable logistic regression analyses were used to evaluate the relationship between NAR and 90-day mortality. The predictive power of NAR was compared with neutrophil count and albumin levels using receiver operating characteristic (ROC) curve analysis. Results Patients in the highest NAR quartile had significantly greater odds of 90-day mortality (adjusted OR 1.74, 95% CI 1.27–2.39, p < 0.001) compared to those in the lowest quartile. The area under the curve (AUC) for NAR was 0.68, demonstrating superior discriminative ability compared to neutrophil count (AUC 0.64) and albumin (AUC 0.60). These findings were consistent across various subgroups, with multivariate analysis confirming the independent predictive value of NAR for mortality in patients with ICH. Conclusions Elevated NAR was independently associated with increased mortality in patients with ICH. NAR is a promising inflammatory marker that could aid in early risk assessment and guide management strategies for patients with ICH.